PENINGKATAN KINERJA PUSTAKAWAN LAYANAN SIRKULASI DI PERPUSTAKAAN DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA SOLOK - Azimah, Rahmatul; Zalmi, Fadhila Nurul Husna; Sari, Shinta Nofita (UIN Imam Bonjol Padang, 2024)
This research aims to analyze the performance improvement of circulation service librarians at the Library and Archives Service of Solok City through the implementation of matrix codes. The methodology used is descriptive quantitative research by distributing questionnaires to 99 respondents consisting of librarians and library visitors. The results show that 45.45% of respondents strongly agree, 54.54% agree, and no respondents disagree or strongly disagree with the use of matrix codes in circulation services. More specifically, it was found that 54.54% of respondents agree that matrix codes simplify and accelerate librarians' work in entering new library members' biodata. The implementation of matrix codes allows visitors to register as library members independently by simply scanning the matrix code and filling out personal data through a digital form. This reduces queues at circulation services and increases time efficiency for librarians in serving other visitors. Additionally, the application of matrix codes also helps reduce paper usage and minimize the risk of errors in recording new member data. This research demonstrates that the implementation of matrix code technology has had a positive impact on improving the performance of circulation service librarians at the Library and Archives Service of Solok City by simplifying and accelerating the registration process for new library members.